2020
DOI: 10.1016/j.chemosphere.2020.126469
|View full text |Cite
|
Sign up to set email alerts
|

The photocatalytic destruction of cinnamic acid and cinnamyl alcohol: Mechanism and the effect of aqueous ions

Abstract: Cinnamic acid was chosen as an exemplar molecule to study the effect of potential contaminants on the kinetics and mechanism of the photocatalytic destruction of hydrocarbons in aqueous solutions. We identify the principal intermediates in the photocatalytic reaction of the acid and corresponding alcohol, and propose a mechanism that explains the presence of these species. The impact of two likely contaminants of aqueous systems, sulfate and chloride ions were also studied. Whereas sulfate ions inhibit the deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…A very different effect was observed over rutile however, with the photocatalytic activity in brines accelerated by a factor of more than two, with the pseudo-first-order rate constant increasing from 2.3 Â 10 À3 min À1 to 4.8 Â 10 À3 min À1 . In contrast to some other reported systems, 9,[33][34][35][36] the higher phenol oxidation rates observed in brines over rutile suggests that there are alternative reaction pathways offered by the presence of chlorine radicals.…”
Section: Photocatalytic Oxidation Of Phenol In Standard Water and Bri...contrasting
confidence: 96%
See 2 more Smart Citations
“…A very different effect was observed over rutile however, with the photocatalytic activity in brines accelerated by a factor of more than two, with the pseudo-first-order rate constant increasing from 2.3 Â 10 À3 min À1 to 4.8 Â 10 À3 min À1 . In contrast to some other reported systems, 9,[33][34][35][36] the higher phenol oxidation rates observed in brines over rutile suggests that there are alternative reaction pathways offered by the presence of chlorine radicals.…”
Section: Photocatalytic Oxidation Of Phenol In Standard Water and Bri...contrasting
confidence: 96%
“…Nevertheless, these results do not eliminate the possibility of small amounts of chloride being adsorbed over the surface of the photocatalyst and acting as hole scavengers, as previously suggested. 8,9 To investigate such a possibility, in the next stage of this work, we compare the ability of such systems to self-trap holes and electrons in their structure. chloride anions.…”
Section: Competitive Adsorption Of Chloride and Hydroxyl Anions Over ...mentioning
confidence: 99%
See 1 more Smart Citation
“…3). [21] Bouleghlimat et al, [8] showed that chlorine radicals formed in this way accelerated the rate of removal of cinnamic acid from an aqueous solution although this also generated chlorine sub-Figure 1. XPS of the photocatalysts post-reaction in the presence of 0.05 M of three different alkali metal chlorides.…”
Section: Discussionmentioning
confidence: 99%
“…One factor that may contribute to the confusion is that, for some systems, although chloride ions open up new reaction pathways and therefore accelerate conversion of the target, the products of these pathways are more resistant to photodegradation and so complete degradation is inhibited. For example, in a recent study [8] related to the photodecomposition of cinnamic acid, we found that the formation of chloride radicals created new pathways resulting in chlorine substituted products. The result was an accelerated rate of decomposition of the cinnamic acid but since the substituted products were resistant to photocatalytic decomposition, there was an overal reduction in the rate of total combustion to CO 2 .…”
Section: Introductionmentioning
confidence: 96%